In vivo imaging of signal decay due to diffusion in the internal field in human knee trabecular bone - Sigmund, Eric; Regatte, Ravinder; Schweitzer, Mark; Cho, Hyungjoon; Song, Yi-Qiao (Diffusion Fundamentals, 2009)
This study presents the first demonstration of the MR signal decay due to diffusion in the internal field (DDIF) for in vivo knee trabecular bone imaging. DDIF contrast was compared with high resolution FLASH, T1, and T2* mapping in healthy volunteers. DDIF maps showed spatial variation, superimposed on a T1 background, reflecting trabecular structure. DDIF and T2* maps showed correlated contrast near dense trabeculae, but their spatial textures differed, suggesting distinct structural sensitivities.